Predictors Of Non-Escherichia Coli Urinary Tract Infection. Issue 11 (November 2016) - Shaikh, Nader; Wald, Ellen R.; Keren, Ron; Gotman, Nathan; Ivanova, Anastasia; Carpenter, Myra A.; Moxey-Mims, Marva; Hoberman, Alejandro
Abstract : We aimed to determine which children are prone to non- Escherichia coli urinary tract infection (UTIs). We included 769 children with UTI. We found that circumcised males, Hispanic children, children without fever and children with grades 3 and 4 vesicoureteral reflux were more likely to have a UTI caused by organisms other than E. coli. This information may guide clinicians in their choice of antimicrobial therapy.